Information and communication technology incorporation for business competitiveness in Norte de Santander’s mining sector (2023)
Currently, Information and Communications Technology (ICTs) are considered great allies in chalking up business strategies, and it has been known that thanks to it, different productive and service sectors have been benefiting in different ways such as increased productivity, improvements in the quality of work of employees, and streamlining of processes, among others. This study aims to describe the current situation of the use of ICTs by the mining sector in Norte de Santander (Northeastern Colombia) and the impact on competitiveness. The developed methodology derives from the positivist paradigm, implementing a quantitative approach. This study was based on an analysis carried out by the mining companies of Norte de Santander on the use of ICTs, and the information was collected through the application of surveys. From the results obtained by applying the data from the surveys to the running of companies, it could be inferred that companies in the mining sector of Norte de Santander have shortcomings in terms of including ICTs in business strategies and in the use of these tools for employee training. On the other hand, the use of basic technologies and the competitiveness in the supply and demand of products and services are at a medium level. In conclusion, mining companies fail to take advantage of the potential that ICTs offer in the business world, which today is a necessity for competitiveness in a global context marred with crises like the ones caused by the COVID-19 pandemic.